WORKSHOPS AND DEMONSTRATIONS OF MAKING HEALTH PROMOTION MEDIA BASED ON ANIMATED VIDEOS USING SIMPLE APPLICATIONS - Putri, Anna Tasya; Aidha, Zuhrina; Deby A. Lubis, Rini; Lorensyifa, Abdinda; Hasibuan, Serahayati; Rahmadani Lingga, Suci; Silvia, Vanny (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
The rapid development of technology can increase access to communication and health information so that it is easily spread widely through the reach of the Internet network. The dissemination of health information through health promotion efforts is no longer monotonous because there are currently many internet platforms that can make opportunities for us to disseminate health information. We should balance the development of increasingly advanced technology Therefore, health experts are needed who can make one of the visual video media in the form of animated videos by utilizing simple applications. The method used in this activity is by providing steps for using the application through practice and demonstration. The result of this activity is an increase in participants' understanding before being given a presentation and after being given a presentation by the speaker. It is hoped that after the end of this activity participants can be more expert and willing to learn the progress of other applications and with this activity, participants can add insight.